2021
DOI: 10.1136/bmjopen-2020-043933
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mobile phone usage to access maternal and child healthcare among women of urban slums in Dhaka, Bangladesh: a cross-sectional study

Abstract: IntroductionWith the acute shortage of human resources and infrastructure, mobile phones can be a critical tool for accessing health services and strengthening health systems in Bangladesh. Yet, there is a scarcity of evidence on the use of mobile phones in this context for accessing health services. In this study, we sought to explore the current use of mobile phones for accessing maternal and child healthcare and its determinants among recently delivered women in urban slums of Bangladesh.MethodsThe data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our study reports that the participants with small household sizes (<4) had a higher willingness to provide fingerprints for accessing healthcare services than those with large household sizes. This may be because women with increased household size are often overburdened with household chores and responsibilities [ 35 ], limiting them to seek appropriate and adequate healthcare services using digital fingerprints [ 11 ]. Similarly, a study in Dhaka’s slum areas indicated a decreased tendency among mothers to seek childcare services using fingerprints and mobile phones [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study reports that the participants with small household sizes (<4) had a higher willingness to provide fingerprints for accessing healthcare services than those with large household sizes. This may be because women with increased household size are often overburdened with household chores and responsibilities [ 35 ], limiting them to seek appropriate and adequate healthcare services using digital fingerprints [ 11 ]. Similarly, a study in Dhaka’s slum areas indicated a decreased tendency among mothers to seek childcare services using fingerprints and mobile phones [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A two-stage cluster random sampling approach was employed to select 458 participants from Dhaka city’s eight randomly selected urban slums. The sample size calculation and the details of the study design can be found elsewhere [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations